Market microstructure – a high frequency analysis of volume and volatility intraday patterns across the Brazilian stock market. - Da Costa, Alexandre Silva; Ceretta, Paulo Sergio; Müller, Fernanda Maria (Revista de Administração da UFSM, 2015)
We investigate market microstructure with high frequency data for all stocks that participate in the Ibovespa index, the most influent index in South America. Market microstructure has been widely investigated in developed markets however not many studies focus on developing countries such as Brazil. We modeled volatility with a straightforward method using standard deviation as proxy, and classified the volume traded of all Ibovespa stocks in every 10 minutes interval of the trading days sampled. In the end, we found similarities of previous investigations documented in financial literature such as the stylized facts L-shape pattern for volatility and the U-shape for volume. One interesting finding is that during the most active trading time, the interval that comprises the closing call, volatility slumps; on the other hand, the second most active trading time, the opening, displays extreme volatility.